(untitled) (Journal of Academic Research, 2019)
The Enzymatic coagulation time (ECT) was determined. The effect of pH, temperature, and added ammonium chloride on the coagulation time as well as the release of NPN by the action of rennet were also studied. The results show that increasing milk pH value increase the ECT. The ECT of camel milk at pH 6.6 was 5.5 times lower than at pH 7.0. The results indicated that Enzymatic coagulation of camel milk (ECT) responses in a similar manner in which bovine milk coagulation responses to changes in temperature and pH. Preheating of camel milk causes an increase in the ECT at different pH values. The amounts of NPN soluble in 2% trichloro acetic acid (TCA) and 12 % TCA released at 90% of ECT, were 6.8 and 5.4 mg/100 ml respectively. addition of 5ml mol/l ammonium chloride to camel milk leads to higher increase in the Enzymatic coagulation time of camel milk (ECT) in compares with that increase caused by preheating of milk. This means, that the response to changes in pH, temperature and ammonium concentration is the same for camel and bovine milk.